Neuropeptide Y and Metabolism Syndrome: An Update on Perspectives of Clinical Therapeutic Intervention Strategies - Huang, Yinqiong; Lin, Xiahong; Lin, Shu (Frontiers in Cell and Developmental Biology, 2021)
Through the past decade of research, the pathogenic mechanisms underlying metabolic syndrome have been suggested to involve not only the peripheral tissues, but also central metabolic regulation imbalances. The hypothalamus, and the arcuate nucleus in particular, is the control center for metabolic homeostasis and energy balance. Neuropeptide Y neurons are particularly abundantly expressed in the arcuate of the hypothalamus, where the blood-brain barrier is weak, such as to critically integrate peripheral metabolic signals with the brain center. Herein, focusing on metabolic syndrome, this manuscript aims to provide an overview of the regulatory effects of Neuropeptide Y on metabolic syndrome and discuss clinical intervention strategy perspectives for neurometabolic disease.